Opioid Sparing Analgesics in Spine Surgery - Logan A. Reed; Mihir Patel; Kevin Luque; Steven M. Theiss (Advances in Orthopedics, 2022)
Combinations of various nonopioid analgesics have been used to decrease pain and opioid consumption postoperatively allowing for faster recovery, improved patient satisfaction, and decreased morbidity. These opioid alternatives include acetaminophen, NSAIDs, COX-2 specific inhibitors, gabapentinoids, local anesthetics, dexamethasone, and ketamine. Each of these drugs presents its own advantages and disadvantages which can make it difficult to implement universally. In addition, ambiguous administration guidelines for these nonopioid analgesics lead to a difficult implementation of standardization protocols in spine surgery. A focus on the efficacy of different pain modalities specifically within spine surgery was implemented to assist with this standardized protocol endeavor and to educate surgeons on limiting opioid prescribing in the postoperative period. The purpose of this review article is to investigate the various opioid sparing medications that have been used to decrease morbidity in spine surgery and better assist surgeons in managing postoperative pain. Methods. A narrative review of published literature was conducted using the search function in Google scholar and PubMed was used to narrow down search criteria. The keywords “analgesics,” “spine,” and “pain” were used.